Blue Persistent Phosphor of YSiO2N:Ce3+ Developed by Codoping Sm3+ or Tm3+ Ions and Thermoluminescence Analysis of Their Trap Distributions. Issue 5 (17th January 2022) - Kitagawa, Yuuki; Ueda, Jumpei; Tanabe, Setsuhisa
Abstract : By estimating the trap depth from the relative position of the zigzag curve of divalent lanthanoid ions and conduction band bottom, the YSiO2 N:Ce 3+ ‐based blue persistent phosphors are developed, and their persistent luminescence and thermoluminescence properties are characterized to identify the electron trap distributions. Taking the nephelauxetic effect caused by covalent nitrogen into account for the vacuum referred binding energy diagram, it is predicted that Tm 3+ and Sm 3+ ions with the trap depth of 0.726 and 1.04 eV are an optimal codopant to obtain Ce 3+ persistent luminescence. The prepared YSiO2 N:Ce 3+ ‐Ln 3+ (Ln = Sm or Tm) samples enhance the Ce 3+ : 5 d → 4 f blue persistent luminescence intensity. In the thermoluminescence glow curves, the Ce 3+ singly doped sample shows two glow peaks related to intrinsic defects; on the other hand, the Ln 3+ codoped samples show an additional glow peak related to the Ln 3+ traps. The thermoluminescence glow curve analyses through the initial rise method combined with the thermal cleaning and trap density methods reveal that the electron traps of Ln 3+ ‐related defects have a distribution with ≈0.25 eV width and depths of 0.802 eV (Tm 3+ ) and 1.10 eV (Sm 3+ ). Abstract : The vacuum referred binding energy diagram for the YSiO2 N:Ce 3+ phosphor is constructed to predict the optimal codopant lanthanoid ions with proper electron trap depth for persistent luminescence. Codoping with Sm 3+ or Tm 3+ ions successfully enhances the Ce 3+ blue persistent luminescence. Thermoluminescence glow curve analyses reveal that Sm 3+ and Tm 3+ form the electron trap distribution below the conduction band bottom.